Identifikasi Pengaruh Profitabilitas Dan Likuiditas Terhadap Kebijakan Dividen Dengan Kepemilikan Manajerial Sebagai Variabel Moderating Di Perusahaan Manufaktur Asean Tahun 2019-2022 - Hervina, Rosilia; Hertina, Dede (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
The purpose of this study is to ascertain, in ASEAN manufacturing firms, the impact of profitability, liquidity, and managerial ownership as moderating factors on dividend policy between 2019 and 2022. The panel data regression approach is used in this study. Secondary data, specifically documentation from ASEAN Manufacturing businesses offering statistics for 2019–2022, is the source of the data. The data analysis approach employs the following tests: multicollinearity, autocorrelation, heteroscedasticity, normality, moderated regression analysis, classical assumption test, and descriptive statistical test using the Eviews 12 application. The results indicate that profitability has a major impact on dividend policy. The data indicates that there is no significant relationship between managerial ownership and dividend policy, with a significance value of 0.7171 > 0.05 and a negative coefficient value. In addition, managerial ownership is unable to mitigate the impact of profitability and liquidity on dividend policy.